The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2147/opth.s372011
|View full text |Cite
|
Sign up to set email alerts
|

Open Globe Injuries: Review of Evaluation, Management, and Surgical Pearls

Abstract: Ocular trauma may either be closed globe or open globe. Open globe injuries are full-thickness defects of the eyewall and are often differentiated by the mechanisms of injury from which they are caused: sharp or blunt trauma. They are ocular emergencies and can lead to substantial visual morbidity. Without timely intervention, damage is irreversible and leads to permanent vision loss. The goals of evaluation are to identify the mechanism of injury, characterize the extent of injury, and gather relevant history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…Intraocular pressure is one of the important factors to maintain the homeostasis of the eye. Severe ocular trauma may result in damage to the iris and the ciliary body or loss of ocular contents due to a ruptured globe, affecting intraocular pressure [17] . In our research, we found the intraocular pressure of 91.8% of patients remained in the normal range after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Intraocular pressure is one of the important factors to maintain the homeostasis of the eye. Severe ocular trauma may result in damage to the iris and the ciliary body or loss of ocular contents due to a ruptured globe, affecting intraocular pressure [17] . In our research, we found the intraocular pressure of 91.8% of patients remained in the normal range after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…40,42 Given these drawbacks of cyanoacrylate glue, it should be reserved for cases when suturing fails to create a watertight wound, which is often encountered with stellate corneal wounds that have poor tissue apposition. 3,43 When applied, care should be taken to only apply glue to the laceration edges, and once polymerization is complete, a Seidel test should be performed to confirm adequate sealing. Finally, a soft BCL is applied in all cases of cyanoacrylate glue use to avoid irritation and decrease the chance of glue dislodgment.…”
Section: Alternative Methods Of Globe Closure: Contact Lenses and Ocu...mentioning
confidence: 99%
“…Absorbable Vicryl sutures are sometimes used instead of Nylon in patients where suture removal without sedation is difficult, such as in children or individuals with intellectual disabilities. 3 Conjunctiva is most often closed with absorbable 8-0 Vicryl sutures. While in general, we do not advise repairing wounds that extend past the muscle insertions, for the rare open globe injuries that require removing and/or reattaching extraocular muscles, 6-0 Vicryl on a spatulated needle is most often used for muscle imbrication and reattachment.…”
Section: Suturesmentioning
confidence: 99%
See 2 more Smart Citations